2014
DOI: 10.4137/cment.s16399
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT in the Assessment of Treatment Response after Oncologic Treatment of Head and Neck Squamous Cell Carcinoma

Abstract: BACKGROUNDIn many centers, 18F-fluorodeoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT) is used to monitor treatment response after definitive (chemo)radiotherapy [(C)RT] for head and neck squamous cell carcinoma (HNSCC), but its usefulness remains somewhat controversial. We aimed at assessing the accuracy of FDG-PET/CT in detecting residual disease after (C)RT.METHODAll HNSCC patients with FDG-PET/CT performed to assess treatment response 10–18 weeks after definitive (C)RT at our insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Reports of improved diagnostic accuracy when PET/CT is employed for HNSCC at or after this time-point reflect the preceding resolution or reduction in treatmentinduced inflammation. 9,11,12 In the current study's patient cohort, which included exclusively sinonasal sites of malignancy, the period of treatment-induced inflammation endured for up to twice the duration (ࣙ 5 months) observed in deep tissue sites of the head and neck. These findings concur with clinical experience that suggests the sinonasal skull base responds to oncologic treatment in a manner that is distinct from other head and neck subsites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports of improved diagnostic accuracy when PET/CT is employed for HNSCC at or after this time-point reflect the preceding resolution or reduction in treatmentinduced inflammation. 9,11,12 In the current study's patient cohort, which included exclusively sinonasal sites of malignancy, the period of treatment-induced inflammation endured for up to twice the duration (ࣙ 5 months) observed in deep tissue sites of the head and neck. These findings concur with clinical experience that suggests the sinonasal skull base responds to oncologic treatment in a manner that is distinct from other head and neck subsites.…”
Section: Discussionmentioning
confidence: 99%
“…8 The reduced accuracy of PET/CT in the early posttreatment setting has largely been attributed to its limited ability to distinguish residual disease from treatment-induced inflammatory changes. 9,10 This inherent weakness of PET/CT has prompted considerable interest within the head and neck literature to determine the optimal time window for PET/CT in the evaluation of treatment response. Several studies, including 2 systematic reviews with meta-analyses, have identified 10 to 12 weeks posttreatment as the ideal time-point for improved diagnostic accuracy of PET or PET/CT, insofar as differentiating persistent viable disease from posttreatment inflammation for deep tissue sites of the head and neck.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that posttreatment PET assessment can be used to avoid unnecessary planned neck dissection even in the presence of nodal abnormalities on CT if they become negative on PET [60, 61]. Keski-Säntti et al [62] reported that PET/CT conducted about 3 months after therapy has sensitivity, specificity, positive predictive value (PPV), and NPV of 59%, 94%, 71%, and 91% for detecting residual disease in the primary sites, and 95%, 100%, 100%, and 93% in the nodes, respectively. Recently, Anderson et al [63] used SUV measurements at 60, 90, and 120 minutes and found that change of maximum SUV slope after 90 minutes more accurately identified non-recurrence in positive or equivocal sites than using SUV at one point.…”
Section: Treatment Response Monitoring and Predictionmentioning
confidence: 99%
“…18 F-FDG PET is used for the diagnosis, staging, and restaging of HNSCC patients. Unfortunately 18 F-FDG PET has a false positive rate of 23%–30% in HNSCC patients, 7 , 8 , 9 , 10 which may necessitate further diagnostic evaluation and tissue sampling as well as potentially delaying therapy. These current limitations and the critical need for improved diagnostic, quantitative and prognostic stratification of HNSCC patients before, during and after definitive therapy are recognized by the interdisciplinary treatment team.…”
Section: Squamous Cell Carcinoma and The Roles Of Conventional Imaginmentioning
confidence: 99%